"What is Palliative Care?": Variability in Content of Palliative Care Informational Web Pages. (April 2017) - Kozlov, Elissa; Carpenter, Brian D.
Background and Aim: Americans rely on the Internet for health information, and people are likely to turn to online resources to learn about palliative care as well. The purpose of this study was to analyze online palliative care information pages to evaluate the breadth of their content. We also compared how frequently basic facts about palliative care appeared on the Web pages to expert rankings of the importance of those facts to understanding palliative care. Design: Twenty-six pages were identified. Two researchers independently coded each page for content. Palliative care professionals (n = 20) rated the importance of content domains for comparison with content frequency in the Web pages. Results: We identified 22 recurring broad concepts about palliative care. Each information page included, on average, 9.2 of these broad concepts (standard deviation [SD] = 3.36, range = 5-15). Similarly, each broad concept was present in an average of 45% of the Web pages (SD = 30.4%, range = 8%-96%). Significant discrepancies emerged between expert ratings of the importance of the broad concepts and the frequency of their appearance in the Web pages ( r τ = .25, P > .05). Conclusion and Implications: This study demonstrates that palliative care information pages available online vary considerably in their content coverage. Furthermore, information that palliative care professionals rate as important for consumers to know is not always included in Web pages. We developed guidelines for information pages for the purpose of educating consumers in a consistent way about palliative care.